The Role of Flavonoids in Mitigating Oxidative Stress: Mechanisms, Applications and Therapeutic Potential - Trivedi, Rahul (Asian Journal of Pharmaceutics (AJP), 2025)
Oxidation is a fundamental aspect of aerobic life processes, involving a reaction in which either electrons or hydrogen are transported from an element to an oxidizing mediator, resulting in the creation of free radicals. Oxidative stress is generally a result of an inequity between reactive oxygen species production and the antioxidant level of a biological system. This is the key factor in the advancement of numerous pathological conditions, such as cardiovascular and neurodegenerative disorders. Flavonoids are an extraordinary class of plant secondary metabolites that have been traditionally utilized as medicines, offering scientifically validated therapeutic benefits. The use of phytochemicals, particularly flavonoids, in the prevention and treatment of diseases is well recognized. Fruits, as well as green vegetables, are natural sources of flavonoids. For humans, recent studies have primarily concentrated on the beneficial effects of flavonoids on well-being. The flavonoids are classified into six different subclasses based on their ring structure. In the present review work, we have focused on the effect of flavonoids and its mechanism in reducing oxidative stress and, ultimately, various disorders. Flavonoids mainly produce their antioxidant effect through neutralizing free radicals, inhibiting enzymes responsible for the generation of free radicals, formation of chelates with metal ions, and stimulating the internal antioxidant defense system. We have also highlighted the therapeutic potential of flavonoids as future therapeutic agents.